Assessment of Patients' and Dentists' Attitudes towards Social Media Usage - Amnah Aqeel Alrashidi,; Mohammed K. Alzamzami,; Yousef obaidmana Aldarami,; Dr. majid nooraldeen alyamani,; Ayshah Hamad Almtairy,; Dr. Ghalibhamad Aljedani, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:The rapid integration of social media into healthcare has transformed communication between professionals and patients, including within dentistry. As dental practices increasingly use social media for engagement and marketing, it is essential to understand patients’ and professionals’ perspectives on these platforms. While social media offers an avenue for education, practice promotion, and patient engagement, it also presents concerns regarding professionalism, privacy, and boundaries. This study aims to assess patient attitudes towards social media use by dental practices and to explore the factors influencing dental practice choice. Methods:This cross-sectional study recruited participants through social media (WhatsApp, LinkedIn, Facebook), using an online questionnaire to collect data from a sample of adults aged 18 and older. The survey comprised 19 questions across four sections: informed consent, sociodemographics, patient behavior, and factors influencing dental practice choice. Descriptive statistics and Pearson’s Chi-square tests were used to analyze relationships between variables. A final sample of 503 responses was analyzed after applying exclusion criteria. Results:Of 503 respondents, 41.4% had engaged with their dental practice’s social media, while 7.2% actively followed them online. Engagement was higher among those who had recently switched providers, with the practice’s website being the most commonly visited platform. Respondents who had changed providers within the last year were more likely to report that social media influenced their decision. The quality of facilities and technology was ranked as the most important factor in choosing a dental practice, while social media presence was considered the least influential. Conclusion:Social media plays a growing yet nuanced role in dentistry, with patients more likely to consult online information when changing practices. While essential for marketing and patient engagement, social media's influence on practice choice remains secondary to traditional factors like facility quality and personal recommendations. Clearer guidelines may help dental professionals navigate the advantages and ethical challenges of social media use in patient interactions, supporting informed and secure engagement for both parties.